Digital governance leveraging urbanization and fintech synergies for sustainable development in BRICS - Chenyu Zhang (Scientific Reports)
Abstract This study explores the relationship between Financial Technology (Fintech) and ecological sustainability, addressing a critical gap in the literature where prior research has primarily focused on the economic and societal impacts of fintech, overlooking its potential environmental benefits. Specifically, the study investigates whether fintech adoption in urban areas contributes to ecological sustainability, offering insights into how fintech can be leveraged to promote sustainable urban development and support global environmental goals. Utilizing a comprehensive panel dataset covering all BRICS nations from 2000 to 2022, the study employs advanced econometric techniques, including second-generation unit root tests, the Westerlund cointegration approach, and the Method of Moments Quantile Regression (MMQR). Additionally, the Augmented Mean Group (AMG) method is used to assess the robustness and stability of the findings. The results suggest that a 10% increase in fintech adoption in urban areas can reduce pollution by 2.3% in the first quantile, highlighting fintech’s potential to improve environmental quality in BRICS countries. However, urbanization has a detrimental impact on environmental conservation, with a 10% rise in urban population leading to a 5.5% increase in pollution in the first quantile. Encouragingly, a 10% increase in the interaction between fintech and urbanization can boost CO2 emissions by 0.02%, as indicated by robustness checks. The study recommends that governments need stringent policies for the promotion of fintech in urban areas to enhance ecological sustainability. Implementing smart city initiatives can further mitigate urban pollution, contributing to the achievement of environmental objectives in BRICS nations.